2018
DOI: 10.1155/2018/3985082
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis and Inhibition of Epithelial Mesenchymal Transition by α‐Mangostin in MG‐63 Cell Lines

Abstract: Osteosarcoma is the most common bone primary malignant tumor and nearly 30% of patients still die from osteosarcoma due to metastasis or recurrence. Thus, it is necessary to develop effective new chemotherapeutic agents for osteosarcoma treatment. α-Mangostin is a xanthone derivative shown to have antioxidant and anticarcinogen properties. However, the molecular mechanisms underlying the antimetastatic effects of osteosarcoma remain unclear. In metastasis progression, epithelial mesenchymal transition (EMT) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The growth inhibition by this extract could also be caused by the content of active substance namely α-mangostin. α-mangostin which is the major component of EEMP is capable to induce the cell death in oral squamous cell carcinoma cell (Kwak et al 2016) and to induce the apoptosis in human osteosarcoma cell line MG63 (Park et al 2018). α-mangostin has been shown to inhibit the proliferation pathway through p38 mitogen-activated protein kinase (MAPK) and to induce the apoptosis mechanism by increasing the levels of Bax, followed by the activation of the caspase 3 and caspase 9 (Lee et al 2016).…”
Section: No Target Proteins Interaction Between Brazilein and Amino mentioning
confidence: 99%
“…The growth inhibition by this extract could also be caused by the content of active substance namely α-mangostin. α-mangostin which is the major component of EEMP is capable to induce the cell death in oral squamous cell carcinoma cell (Kwak et al 2016) and to induce the apoptosis in human osteosarcoma cell line MG63 (Park et al 2018). α-mangostin has been shown to inhibit the proliferation pathway through p38 mitogen-activated protein kinase (MAPK) and to induce the apoptosis mechanism by increasing the levels of Bax, followed by the activation of the caspase 3 and caspase 9 (Lee et al 2016).…”
Section: No Target Proteins Interaction Between Brazilein and Amino mentioning
confidence: 99%
“… 16 We assume that the differences in the findings from this study with Xu et al and Park et al were most likely due to the difference in cell types. 15 , 16 The fact that their research was done in naïve cells were the main thing that contributes to this distinction. The difference between naïve cells and resistant cells was explained by Chen et al, who found a different downstream of the MAPK signaling pathway in untreated versus sorafenib-treated HCC cell lines.…”
Section: Resultsmentioning
confidence: 59%
“…Both studies showed that alpha mangostin suppressed EMT.Xu et al reported that alpha mangostin treatment in BxPc-3 and Panc-1 cells resulted in the reduction of EMT markers by inhibiting PI3K/Akt pathways, 15 whereas Park et al showed that alpha mangostin inhibit MAPK Pathways (ERK 1/2, JNK, and p38). 16 However, Park et al also showed that although E-cadherin expressions were increased, Snail protein expression in the dose of 10 µM was elevated significantly. 16 We assume that the differences in the findings from this study with Xu et al and Park et al were most likely due to the difference in cell types.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations